The impact of aluminum impurity on the regenerated lithium nickel cobalt manganese oxide cathode materials from spent LIBs. (4th September 2017) - Ren, Jie; Li, Ruhong; Liu, Yuanlong; Cheng, Yarui; Mu, Deying; Zheng, Rujuan; Liu, Jianchao; Dai, Changsong
Abstract : An effective recycling process from spent LIBs has been developed, and the tolerability of aluminum was studied in this work. Abstract : In this paper, an effective recycling process from spent LIBs has been developed. The aluminum residual commonly exists in hydrometallurgy, and also aluminum is considered as a resultant additive in LIB modification, therefore, the tolerability of aluminum was studied in this work. Li[(Ni1/3 Co1/3 Mn1/3 )1− x Al x ]O2 (0.01 ≤ x ≤ 0.05) cathode materials were regenerated from spent ternary LIBs. X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electrochemical measurements were carried out to characterize the performances of all of the samples. XRD and XPS results indicate that Mn and Ni are possibly replaced by Al. When x ≤ 0.03, the initial discharge capacity is up to 170 mA h g −1 at 0.05C between 2.5 and 4.5 V, and more than 100 mA h g −1 at 2C. The results showed that the existence of aluminum of up to x = 0.03 has no significant impact on the cathode materials of Li[(Ni1/3 Co1/3 Mn1/3 )1− x Al x ]O2, and the content surpasses the conventional limitations.